Authigenic neodymium records from sediment core GL1090 for the penultimate glacial termination and Last Interglacial - Bruna Borba Dias; Cristiano Mazur Chiessi; Alexander M Piotrowski; Marília C Campos; Partha S Jena; João M Ballalai; Rodrigo Azevedo Nascimento; Thiago Pereira dos Santos; Igor Martins Venancio; Ali Mashayek; Ana Luiza Spadano Albuquerque (PANGAEA, 2025)
We present authigenic neodymium isotopes (?Nd) values from a mid-depth core in the western South Atlantic to assess changes in deep ocean circulation during the penultimate glacial termination and the Last Interglacial (LIG). Authigenic ?Nd were analyzed on uncleaned mixed planktonic foraminifera from the intervals of the penultimate glacial termination and the LIG. These data were compared to the authigenic ?Nd dataset from the last glacial termination and the Holocene published by Howe et al. (2018, doi:10.1016/j.epsl.2018.03.006). The samples were dissolved, and rare earth elements (REE) were separated from other elements using Eichrom TRUspec™ resin. Neodymium was then extracted from the other REE using Eichrom Lnspec™ resin. Samples were analyzed using a Neptune Plus multi-collector mass spectrometer (MC-ICP-MS). The reported error corresponds to 2 standard deviations of reproducibility of the bracketing standards.